PENGARUH MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU YANG DIMODERASI OLEH BUDAYA ORGANISASI PADA MI SE-KECAMATAN WINONG KABUPATEN PATI (Studi Kasus pada Guru-Guru MI Se-Kecamatan Winong Kabupaten Pati) - Fuad, Sholihul; Srimindarti, Ceacilia (Proceeding SENDI_U, 2015)
This study aimed to examine the effect of motivation and organizational commitment onteacher performance in MI Sekecamatan Winong Pati regency moderated with the organizationculture. The specific objectives of this study was to examine the effect of motivation andorganizational commitment on teacher performance are moderated by the organization culture. Theusefulness of this study is to clarify and extend previous research on the effect motivation andorganizational commitment on teacher performance are moderated organization culture. This studyused a population of teachers in MI Sekecamatan Winong Pati regency much as 107 teachers.Sampling techniques in this study is probability sampling with proportional random samplingmethod. The method used in this research is regression with interaction quasi moderation. Based onthe results of the study can be summarized as follows motivation has no effect on the performance ofteachers, organizational commitment effect on the performance of the teacher, the organizationculture no affect the performance of the teacher, the influence of motivation on teacherperformance is not moderated by organization culture, weaken the influence of organization culturevariable of organizational commitment with teacher performance.Keywords: motivation, organizational commitment, organization culture, the performance ofteachers.